Convergent Validity of Preschool Children's Television Viewing Measures among Low-Income Latino Families: A Cross-Sectional Study - Mendoza, Jason A. (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Television viewing is an important modifiable risk factor for childhood obesity. However, valid methods for measuring children's TV viewing are sparse and few studies have included Latinos, a population disproportionately affected by obesity. The goal of this study was to test the reliability and convergent validity of four TV viewing measures among low-income Latino preschool children in the United States. METHODS: Latino children (n=96) ages 3–5 years old were recruited from four Head Start centers in Houston, Texas (January, 2009, to June, 2010). TV viewing was measured concurrently over 7 days by four methods: (1) TV diaries (parent reported), (2) sedentary time (accelerometry), (3) TV Allowance (an electronic TV power meter), and (4) Ecological Momentary Assessment (EMA) on personal digital assistants (parent reported). This 7-day procedure was repeated 3–4 weeks later. Test–retest reliability was determined by intraclass correlations (ICC). Spearman correlations (due to nonnormal distributions) were used to determine convergent validity compared to the TV diary. RESULTS: The TV diary had the highest test–retest reliability (ICC=0.82, p<0.001), followed by the TV Allowance (ICC=0.69, p<0.001), EMA (ICC=0.46, p<0.001), and accelerometry (ICC=0.36–0.38, p<0.01). The TV Allowance (r=0.45–0.55, p<0.001) and EMA (r=0.47–0.51, p<0.001) methods were significantly correlated with TV diaries. Accelerometer-determined sedentary minutes were not correlated with TV diaries. The TV Allowance and EMA methods were significantly correlated with each other (r=0.48–0.53, p<0.001). CONCLUSIONS: The TV diary is feasible and is the most reliable method for measuring US Latino preschool children's TV viewing.